2023
DOI: 10.1542/peds.2022-058552
|View full text |Cite
|
Sign up to set email alerts
|

Race and Ethnicity Reporting and Representation in Pediatric Clinical Trials

Abstract: BACKGROUND AND OBJECTIVES Representative enrollment of racial and ethnic minoritized populations in biomedical research ensures the generalizability of results and equitable access to novel therapies. Previous studies on pediatric clinical trial diversity are limited to subsets of journals or disciplines. We aimed to evaluate race and ethnicity reporting and representation in all US pediatric clinical trials on ClinicalTrials.gov. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…It is also possible that Black or African American caregivers are reluctant to report concerns about their child’s behavior for fear of the response of health care professionals (eg, may result in reports to child protective services as there is disproportionately higher contact among Black or African American families compared with White families due to structural racism) . Our findings underscore the need for increased cultural sensitivity and understanding of Black or African American families and other historically marginalized populations in pediatric primary care both in terms of clinical practice and research …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is also possible that Black or African American caregivers are reluctant to report concerns about their child’s behavior for fear of the response of health care professionals (eg, may result in reports to child protective services as there is disproportionately higher contact among Black or African American families compared with White families due to structural racism) . Our findings underscore the need for increased cultural sensitivity and understanding of Black or African American families and other historically marginalized populations in pediatric primary care both in terms of clinical practice and research …”
Section: Discussionmentioning
confidence: 82%
“…20 Our findings underscore the need for increased cultural sensitivity and understanding of Black or African American families and other historically marginalized populations in pediatric primary care both in terms of clinical practice and research. 21,22 Being male was associated with the 3 elevated trajectories compared with the LS trajectory group. Males were also more represented in the HI vs MD groups although being female was associated with membership in the MD vs LI groups.…”
Section: Discussionmentioning
confidence: 87%
“…The diversity of children included in clinical research has been examined in prior studies with varying results regarding representation of different racial and ethnic groups . One study analyzing data from 33 federally funded studies evaluating pediatric drugs and devices and enrolling almost 11 000 participants from 2008 to 2020 found no evidence of racial or ethnic bias in enrollment .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these activities, a 2022 report from the National Academies of Sciences, Engineering, and Medicine on the representation of women and underrepresented groups in clinical research concluded that racial and ethnic diversity in clinical trials remained inadequate and largely unchanged over the past 30 years . Although the report did not specifically examine pediatric trial participants, several studies have assessed racial and ethnic diversity in pediatric studies across a spectrum of trial cohorts and presented mixed findings on the level of representation of different patient groups . Given the unique considerations in enrolling children into clinical trials, a focused assessment of the diversity of pediatric participants in NIH-funded clinical trials, including reporting practices for race and ethnicity information, could inform the impact of current policies and identify any remaining gaps in the NIH’s strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The trial was approved by the institutional review boards at all participating sites and was registered with the US Food and Drug Administration (Investigational New Drug application 102 138). Maternal race and ethnicity was self-reported and was assessed in this study because such reporting is important to determine whether there were differences in severity of HIE or in outcomes based on race, and whether the results are generalizable …”
Section: Methodsmentioning
confidence: 99%